2017
DOI: 10.1161/jaha.117.006028
|View full text |Cite
|
Sign up to set email alerts
|

Ectopy on a Single 12‐Lead ECG, Incident Cardiac Myopathy, and Death in the Community

Abstract: BackgroundAtrial fibrillation and heart failure are 2 of the most common diseases, yet ready means to identify individuals at risk are lacking. The 12‐lead ECG is one of the most accessible tests in medicine. Our objective was to determine whether a premature atrial contraction observed on a standard 12‐lead ECG would predict atrial fibrillation and mortality and whether a premature ventricular contraction would predict heart failure and mortality.Methods and ResultsWe utilized the CHS (Cardiovascular Health) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
2
33
0
2
Order By: Relevance
“…PACs are associated with increased AF risk and are considered a potential endophenotype of AF. 14 The lack of association in our analysis is consistent with a small randomized study reporting no effect of oral magnesium supplementation on PAC burden. 15 As a whole, these findings suggest that magnesium may reduce AF risk through pathways other than facilitation of atrial ectopy.…”
Section: Discussionsupporting
confidence: 90%
“…PACs are associated with increased AF risk and are considered a potential endophenotype of AF. 14 The lack of association in our analysis is consistent with a small randomized study reporting no effect of oral magnesium supplementation on PAC burden. 15 As a whole, these findings suggest that magnesium may reduce AF risk through pathways other than facilitation of atrial ectopy.…”
Section: Discussionsupporting
confidence: 90%
“…ECG is a crucial diagnostic modality, which examines changes in cardiac electrical activity, e.g. rhythm disturbances [33,34]. ECG uses skin surface electrodes, which detect the electrical current spread throughout the body, caused by the cardiac activity.…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%
“…Premature ventricular complex can be detected in up to 70% of Holter recordings of ambulatory healthy and young adults (Von Rotz et al, ). In the literature, it was suggested that PVCs can lead to the deterioration of left ventricular (LV) function and subsequent LV dilatation which is defined as PVC induced cardiomyopathy (PVC‐CMP) (Agarwal et al, ; Nguyen et al, ; Niwano et al, ). Recent studies demonstrated that PVC‐CMP could be reversed upon the suppression of PVCs by antiarrhythmic drugs (AAD) or catheter ablation (Duffee, Shen, & Smith, ; Oomen, Dekker, & Meijer, ; Yarlagadda et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Premature ventricular complex can be detected in up to 70% of Holter recordings of ambulatory healthy and young adults (Von Rotz et al, 2017). In the literature, it was suggested that PVCs can lead to the deterioration of left ventricular (LV) function and subsequent LV dilatation which is defined as PVC induced cardiomyopathy (PVC-CMP) (Agarwal et al, 2017;Nguyen et al, 2017;Niwano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%